2020
DOI: 10.1016/j.sdentj.2019.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of salivary pH on coating durability of two different aesthetic archwire coatings under a simulated intraoral environment

Abstract: Objectives This study compared the effects of normal salivary pH, and acidic pH found in patients with poor oral hygiene, on the durability of aesthetic archwire coated with epoxy resin and polytetrafluoroethylene (PTFE). Methods The posterior parts of the archwires were sectioned into 20 mm segments (N = 102) and divided among six groups. Four groups were treated with different pH levels and two served as controls. The specimens were immersed in individual test tubes c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…However upon clinical use, surface roughness was shown to significantly increase in several tested coated archwires including Everwhite archwires [ 21 ]. The epoxy resin coating was reported to be unstable following exposure to saliva in several previous studies [ 15 , 22 24 ] ranging from increased surface roughness to tearing and coating loss in multiple locations. This instability, which is manifested clinically as unpleasant discolouration and rupture of the coating layer [ 25 ], can be attributed to the hydrophilic property of resins [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…However upon clinical use, surface roughness was shown to significantly increase in several tested coated archwires including Everwhite archwires [ 21 ]. The epoxy resin coating was reported to be unstable following exposure to saliva in several previous studies [ 15 , 22 24 ] ranging from increased surface roughness to tearing and coating loss in multiple locations. This instability, which is manifested clinically as unpleasant discolouration and rupture of the coating layer [ 25 ], can be attributed to the hydrophilic property of resins [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…35,36 Despite this, potentially, under the test conditions used for this study, the surface coating material from this orthodontic wire may have slightly degraded, increasing its roughness and consequently its ability to retain biofilm. 37 It is also possible that the increase in absorbance could have been a consequence of increased stain absorption by the wire coating. Although higher biofilm accumulation on this PTFE coating could indicate an increased risk to develop dental caries, future in vivo studies with these wires are needed to further assess the attraction of pathogens and biofilm accumulation differences as surface changes during placement can have significant changes in biofilm adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…However, even though these protective oxide films are present on the metal surface, metal ions can still be released. Not only is the protective oxide layer susceptible to both mechanical and chemical disruption, but the oxide film can also slowly dissolve as the wire is exposed to oxygen from the surrounding medium [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [ 38 ] reported that the PTFE coating had poor stability owing to the thinner coating layer. Moreover, this deterioration and coating loss exposes the core metal wire, causing absorption of large amounts of hydrogen because the titanium attracts hydrogen and undesirable aesthetic effects such as discoloration and ruptures that appear when the archwires are used clinically [ 37 ]. This results in a gradual change in the mechanical properties that must be considered.…”
Section: Discussionmentioning
confidence: 99%